(untitled) (Anclajes, 2019)
In Letter to the Spanish Americans, Juan Pablo Viscardo y Gusmán understands Independence as a renunciation of a covenant and as emancipation of a guardianship. The fluctuation between both interpretations corresponds to the reference to two traditions –Spanish Neo-Scholasticism and Enlightenment thought–, but also to two different narratives of independence itself.